The vine tea flavonoids extraction by ultrasound-enzyme-assisted and its consequences for antioxidant efficacy and gut microbiota in rats - Hao Shi; Meng-ling Qin; Qing-yuan Liu; Tao Yang; Yu-ling Hu; Yun Wang; Jing Wang (Food and Agricultural Immunology)
Vine tea is rich in flavonoids, and this study explored their high-value utilization of vine tea flavonoids (VEF). Usingresponse surface methodology (RSM), optimal ultrasound-enzymatic extraction conditions were determined: 75% ethanol, 1:30 solidliquidratio, 56 min ultrasonication, and enzyme concentrations of 2.1% papain, 2.3% pectinase, and 2.6% cellulase, achieving a 25.10%VEF yield. Purified VEF (PVEF) exhibited superior antioxidant activities, including in vitro, in vivo, and gut microbe-mediated effects.PVEF showed higher free radical scavenging and anti-lipid peroxidation than VC. Additionally, PVEF also enhanced beneficial gutbacteria, GSH-Px activity, and related gene (Gpx1, Gclm) and protein levels while reducing liver ROS in rats, outperforming the Xue ZhiKang group. Specifically, the H-PVEF group showed 34.98% and 49.47% higher GSH-Px activity than the control and model groups,respectively. In conclusion, ultrasound-enzyme-assisted extraction significantly boosts VEF yield, and PVEF demonstrates potentantioxidant properties, supporting its potential in functional foods and pharmaceuticals.